# The pth, qth and rth terms of an A.P. are a, b, c, respectively. Show that(q – r )a + (r – p )b + (p – q )c = 0

Let A = first term of the AP.
and
Let d = common difference of the AP

Let n be the number of terms of the A.P.

It is known that the nth term of an A.P. is given by -

an = a + (n –1) d

∴ pth term of A.P. is given by -
a = A + (p - 1).d.......(1)

qth term of A.P. is given by -
b = A + (q - 1).d.......(2)

rth term of A.P. is given by -
c = A + (r - 1).d........(3)
Subtracting (2) from (1) , (3) from (2) and (1) from (3), we get
a - b = (p - q).d......(4)
b - c = (q - r).d........(6)
c - a = (r - p).d.......(6)

Multiply (4),(6) and (6) by c, a and b respectively, we have

c.(a - b) = c.(p - q).d......(4)
a.(b - c) = a.(q - r).d........(6)
b.(c - a) = b.(r - p).d.......(6)

Adding (4),(6) and (6), we get -

c.(a - b) + a.(b - c) + b.(c - a) = c.(p - q).d + a.(q - r).d + b.(r - p).d
ac - bc + ab - ac + bc - ab = a.(q - r).d + b.(r - p).d + c.(p - q).d

a.(q - r).d + b.(r - p).d + c.(p - q).d = 0

Now since d is common difference, it should be non zero
Hence
a(q - r) + b(r - p) + c(p - q) = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Interactive quiz on inequalities involving AM and GM45 mins  Check Your progress Part 2| Interactive Quiz: Sequence & Series47 mins  Sequence & Series (Lecture 1)56 mins  Sequence & Series (Lecture 5)42 mins  Sequence & Series (Lecture 7)37 mins  Use of sigma in finding sum42 mins  Quick Recap lecture of Sequence & Series56 mins  General Term of Miscellaneous progression46 mins  Improve your understanding of AP & GP27 mins  Geometric Progression58 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 